Creating Memorandums of Understanding/Agreement with Affiliate Organizations of 4-H - Marilyn N. Norman; Joy C. Jordan (EDIS, 2008)
Revised! 4H2.51, an 8-page factsheet by Marilyn N. Norman and Joy C. Jordan, explains how 4-H can effectively and productively work together with other nonprofit groups by drafting Memorandums of Understanding to guide the process and make it work smoothly. Includes 3 sample Memorandums. Revised to reflect policy changes. Published by the UF Department of Family, Youth and Community Sciences, January 2008.